2011
DOI: 10.3324/haematol.2011.050500
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking the functional hematopoietic stem cell niche in vitro: recapitulation of marrow physiology by hydrogel-based three-dimensional cultures of mesenchymal stromal cells

Abstract: BackgroundA culture system that closely recapitulates marrow physiology is essential to study the nichemediated regulation of hematopoietic stem cell fate at a molecular level. We investigated the key features that play a crucial role in the formation of a functional niche in vitro. Design and MethodsHydrogel-based cultures of human placenta-derived mesenchymal stromal cells were established to recapitulate the fibrous three-dimensional architecture of the marrow. Plastic-adherent mesenchymal stromal cells wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
118
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(121 citation statements)
references
References 62 publications
1
118
0
2
Order By: Relevance
“…This is in agreement with other 3D culture approaches [32,38,51], which collectively demonstrate that levels of key endosteal factors, such as FN, VN, OPN and ALP, are enhanced in 3D compared to 2D controls.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This is in agreement with other 3D culture approaches [32,38,51], which collectively demonstrate that levels of key endosteal factors, such as FN, VN, OPN and ALP, are enhanced in 3D compared to 2D controls.…”
Section: Discussionsupporting
confidence: 78%
“…MSCs are sourced from multiple tissues, including bone marrow [49] and placenta [50]. Bone marrow-derived MSCs (bmMSCs) have been used to develop in vitro models of the HSC niche [32,38,51]. However, plMSCs are more accessible than bmMSCs in terms of their isolation procedures and cell numbers per donor [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of this attachment will be mediated by the ECM binding integrins present on the cell surface. The ECM motifs are either provided directly by the material used (gelatin, collagen, fibronectin), by serum adhesion proteins (Kobayashi et al, 2005;Dodo et al, 2013), or early deposition of ECM by the cells themselves (Pearlstein et al, 1980;Desai et EM Schutgens et al Biomaterials for intervertebral disc regeneration al., 2014;Jin et al, 2007;Sharma et al, 2012;Xu et al, 2013). Integrin-mediated cell-matrix binding not only affects chondrogenic cell survival and proliferation in vitro and in vivo (Gilchrist et al, 2007;Loeser, 2014), but is also involved in cell differentiation by regulating the response to materials with different mechanical properties.…”
Section: Extracellular Matrix-cell Interactionmentioning
confidence: 99%
“…It was previously shown that arterioles are associated with both quiescent NG2 + niche cells and HSCs, suggesting that the vessel itself may be a critical gatekeeper of stem cell quiescence in the BM (Kunisaki et al, 2013). A culture system that closely recapitulates marrow physiology is essential to study the niche-mediated regulation of HSC fate (Sharma et al, 2012).…”
Section: Introductionmentioning
confidence: 99%